The study of biochemical monitoring of training & nutritious invigorant mode of excellent bicycle athlete during the period of winter training - Liu, B.; Gao, W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The study's object was Zhao Haijuan, a Chinese famously excellent bicycle athlete, who has gained the champion of World Cup and Asia Sports Game. She has been observed concerning physical changes of biochemical and nutritious invigorant during her winter training from 11-12,2003. The indexes selected ware: Hemoglobin (Hb), Testosterone(T) and Creatine kinase (CK).